The Fluid City Paradigm Waterfront Regeneration as an Urban Renewal Strategy - Carta, Maurizio; Ronsivalle, Daniele (UNIPA Springer Series, 2016)
This book presents a new paradigm of knowledge and action with respect to urban waterfronts, the "fluid city paradigm", explaining its methodological framework and describing an integrated and creative planning approach in which waterfront regeneration is pursued as a key urban renewal strategy. The book focuses especially on the WATERFRONT project ("Water And Territorial policiEs for integRation oF multisectoRial develOpmeNT"), which was funded jointly by Italy and Malta with the goal of developing common guidelines, strategies, and operational tools for the planning of coastal areas based on cross-border exchange of experiences. In the described approach, the waterfront is recognized as having a wider identity, acknowledging the complexity of the relationship between seaport and town and taking into account the physical and environmental components of human settlement, infrastructure, and productive and recreational activities. Detailed attention is paid especially to the process of renewal in the port city of Trapani, with discussion of the implemented actions, plans, and programs. The book also examines the practices adopted to transform city-port relationships across Europe in pursuit of innovative and sustainable development.